Studies on Phytochemical and Antioxidant Activity of Wild Apricot (Prunus armeniaca L.) and Pomegranate (Punica granatum) - Sharma, Somesh; Thakur, Aman deep; Chauhan, Priyanka; Thakur, Ashok K. (International Journal of Economic Plants, 2017)
Wild Apricot (Prunus armeniaca L.) is one of the important wild plant found in higher ranges of western Himalayan region. The fruit is a rich source of antioxidants especially flavonoids and carotenoids and still remains underutilized with low economic value. Pomegranate (Punica granatum) belongs to the Punicaceae family but is also one of the commercially important fruit which is extensively cultivated in many tropical and subtropical regions such as Iran. Pomegranate is also a rich source of anthocynins, vitamin C and antioxidant. In the present studies the fruits of wild apricot and pomegranate grown in Himachal Pradesh have been studied for their physicochemical and nutraceutical values. The physico-chemical properties studied such as weight, colour, pulp yield, total soluble solids, titratable acidity, pH, total sugar, reducing sugar, total phenols, ascorbic acid and carotenoids. The total phenols content was higher (240±12 mg l-1) in pomegranate and lower (132±8 mg l-1) in case of wild apricot. However, the ascorbic acid content was recorded higher (37±3 mg 100 g-1) in pomegranate fruits then in case of wild apricot (24±2 mg 100 g-1). The qualitative estimation of phytochemicals showed that alkaloid, flavonoid, terpenoid are present in both the fruits where as saponin, phlobatannin and cardiac glycosides were absent and tannin was present in pomegranate fruit only. Furthermore, the DPPH antioxidant activity of pomegranate was found 75% where as in case of wild apricot it was 68%. The FRAP antioxidant power of pomegranate 976 µmol Fe (II) g-1 whereas in wild apricot 308 µmol Fe (II) g-1. Furthermore, the ABTS activity in case of pomegranate was 79% whereas in case of wild apricot was 73%. Higher the antioxidant value more will be the health benefits. Hence, from the present studies it can be concluded that the fruits grown in Himachal Pradesh have potential to be a good source of various nutraceutical compounds.